Covid-19 Pandemic and its implications on society, polity and economy in contemporary India: Some critical reflections - Lahiry, Sujit (South Asian Journal of Socio-Political Studies)
The Covid-19 Pandemic has unfolded as one of the most major and greatest humanitarian crises in the contemporary world. Though it started with China. It soon spread to US and Europe, and subsequently to Asian countries, like India.